Nursing and Global Health: social determinants of health in the training of nurses - Isabel Amélia Costa Mendes; Carla Aparecida Arena Ventura; Laís Fumincelli; Valtuir Duarte de Souza-Junior; Simone de Godoy
ABSTRACT Objective: To evaluate to which extent nursing professors understand how social determinants of health impact on health, and whether the topic is addressed in nursing undergraduate education in Brazil. Method: This is a methodological study carried out with 222 nursing faculty members from Brazilian higher education institutions. The answers of the domain "Social and environmental determinants of health", concerning a questionnaire on "Core Competencies in Global Health", were analyzed. Results: Most professors have over 10 years of experience in nursing higher education. A large part of the participants strongly agreed or agreed on the importance of college subjects related to the above-mentioned topic for the education of the nurses. Conclusion: The professors in this study agreed that social and environmental health determinants must be taught in Nursing school, since it is necessary that nurses value this knowledge, slowly making it a part of the curriculum framework.